Novel insights into the classification of staphylococcal β-lactamases in relation to the cefazolin inoculum effect (2020)
Cefazolin has become a prominent therapy for methicillin-susceptible Staphylococcus aureus (MSSA) infections. However, an important concern is the cefazolin inoculum effect (CzIE), a phenomenon mediated by staphylococcal β-lactamases. Four variants of staphylococcal β-lactamases have been described based on serological methodologies and limited sequence information. Here, we sought to reassess the classification of staphylococcal β-lactamases and their correlation with the CzIE. We included a large collection of 690 contemporary bloodstream MSSA isolates recovered from Latin America, a region with a high prevalence of the CzIE. We determined cefazolin MICs at standard and high inoculums by broth microdilution. Whole-genome sequencing was performed to classify the β-lactamase in each isolate based on the predicted full sequence of BlaZ. We used the classical schemes for β-lactamase classification and compared it to BlaZ allotypes found in unique sequences using the genomic information. Phylogenetic analyses were performed based on the BlaZ and core-genome sequences. The overall prevalence of the CzIE was 40%. Among 641 genomes, type C was the most predominant β-lactamase (37%), followed by type A (33%). We found 29 allotypes and 43 different substitutions in BlaZ. A single allotype, designated BlaZ-2, showed a robust and statistically significant association with the CzIE. Two other allotypes (BlaZ-3 and BlaZ-5) were associated with a lack of the CzIE. Three amino acid substitutions (A9V, E112A, and G145E) showed statistically significant association with the CzIE (P β <0.01). CC30 was the predominant clone among isolates displaying the CzIE. Thus, we provide a novel approach to the classification of the staphylococcal β-lactamases with the potential to more accurately identify MSSA strains exhibiting the CzIE.